Design of a Metal‐Organic Framework with Preset Binding Sites for Crystallographic Visualized Metalation. Issue 10 (8th September 2022) - Wang, Rui; Liu, Bai-Tong; Zhang, Shuo; Huang, Xin-Song; Xie, Lei; Liu, Tian-Fu; Cao, Rong
Abstract : Post‐synthetic modification (PSM) of metal‐organic frameworks (MOFs) has emerged as a powerful method to introduce diverse functional species. However, it's still a challenge to design a robust enough parent matrix with preset binding sites and simultaneously accurate structure information after PSM. In this study, a stable and highly crystalline 3D Mn‐based MOF (MnBTT) is designed where two uncoordinated N atoms on adjacent linkers show appropriate distance and direction for metalation, presenting a crystallographic visualization platform for PSM. It's striking to find that the metalations occur at different positions as MnBTT are post‐modified with Cu and Pd salts, respectively, and this difference can be explained by Irving‐Williams series. The different metalation results bring drastic influence on their structure stability, gas adsorption capacity, and metal valence. These factors further greatly impacted their CO catalytic performance, among which Cu‐modified MnBTT outperforms the others. Therefore, we demonstrate a crystallographic visualization platform with preset binding sites for metalation, shedding light on exploring new functional MOFs for broad application potential. Abstract : In a Mn‐based metal‐organic framework (MOF) with preset N binding sites, the metalation process is crystallographic visualized, and different metal ions are post‐modified at different positions. The obtained Cu and Pd‐modified Mn‐based MOF show great disparity on structure stability and CO catalytic activity, among which Cu outperforms the others.